Design, fabrication, and bending test of shape memory polymer composite hinges for space deployable structures. (May 2018) - Dao, Thanh Duc; Ha, Ngoc San; Goo, Nam Seo; Yu, Woong-Ryeol
Shape memory polymers are smart materials characterized by a recoverability memory effect and a large strain, but their mechanical properties such as low stiffness need to be improved for mechanical applications with large recovering force. Researchers have reported that the characteristics of shape memory polymers can be significantly improved when the shape memory polymers are used with fiber–reinforced composite material. In this study, a carbon fiber fabric-reinforced shape memory polymer composite hinge was designed, fabricated, and characterized for space deployable structure applications. The main idea is that the carbon–epoxy composite itself and the shape memory polymer are combined, which means both epoxy resin and shape memory polymer resin are used together and the epoxy resin remains in a B-stage after curing. As such, the stiffness and shape recovery ratio are increased. The shape memory polymer composite hinge specimens with four plies of carbon fiber fabric and a shape memory polymer were prepared for the experiment. The glass transition temperature, which was 70.9°C, was determined using dynamic mechanical analyzer. The effect of temperature on shape recovery capability was investigated. We investigated the reasons of damage evolution to shape memory polymer composite tapes occurring in the folding and deploying process. To do that, damage to the hinge was observed with a USB digital microscope and a scanning electron microscopy and then explained with ABAQUS analysis. The results confirm that the shape memory polymer composite hinge is a good candidate for an antenna in spacecraft in space.